Analysis of instrumentation system for photovoltaic pyranometer used to measure solar irradiation level - Prisma Megantoro; Muhammad Akbar Syahbani; Sigit Dani Perkasa; Ahmad Rahmad Muzadi; Yusrizal Afif; Agus Mukhlisin; Pandi Vigneshwaran (Institute of Advanced Engineering and Science, 2022)
A pyranometer is a device used to measure the level of solar irradiation. This device has a sensor that measures the density of the electromagnetic flux of solar radiation on a flat plane. The electromagnetic flux density parameter is converted into an electrical parameter in watts per square meter. Pyranometers are used in weather station devices to analyze and predict weather conditions. Solar power generation systems are usually also installed with this device. It is intended to monitor solar irradiation's condition to examine the generating system's performance. This article discusses the photovoltaic-based pyranometer characterization method. The characterization method is carried out to determine the measurement parameters such as accuracy, precision, and hysteresis. Knowing these parameters will make it possible to see the performance of measuring solar irradiation levels by a measuring instrument for solar irradiation levels, like a pyranometer. The characterization method is to compare the measurement results with standard instruments. The solar irradiance level monitoring is also optimal, accurate, and precise with a reliable measurement method.